No evidence for relationship between paternal post-partum depressive symptoms and testosterone or cortisol in first-time fathers - Kotov, Daria A.; Corpuz, Randy (Frontiers in Psychology, 2024)
Male life history strategies are regulated by the neuroendocrine system. Testosterone (T) and cortisol regulate male behaviors including parenting and facilitate managing tradeoffs at key transitions in development such as first-time fatherhood. Both demonstrate fluctuations in the postnatal period, and this presents an opportunity to investigate the role of T and cortisol in postpartum depressive symptoms-comparably less studied in fathers. Prior work on depressive symptoms has yet to integrate insights from the "dual hormone hypothesis (DHH)" which has focused on how T and cortisol interact to jointly regulate traits associated with dominance and status-seeking (i.e., mating effort) but has yet to be included in models of parenting. We use secondary data (Corpuz et al., 2021) to investigate the relationship between DHH and traits ostensibly opposed to status seeking (i.e., depressive symptoms). First-time fathers (n=193) provided morning saliva samples 10 months following parturition and reported on the presence of depressive symptoms (BDI-II). Responses were decomposed into three factors: cognitive, affective, and somatic. Using hybrid latent variable structural equation modeling, we did not find evidence that T predicted variability in depressive symptom factors. We found a null effect for cortisol as well. Finally, we could not find evidence that the DHH variable (T x cortisol interaction) predicted any variability in depressive symptoms. This study contributes to research on the neuroendocrinology of depression in fathers. Discussion focuses on the limitations of sample demographics, timing of saliva and selfreport collection, and the lack of extant theory specific to paternal postpartum depression.